Differentiation of Isolated Small Bowel Crohn’s Disease from Other Small Bowel Ulcerative Diseases: Clinical Features and Double-Balloon Enteroscopy Characteristics - Meng Niu; Zheng-Hao Chen; Meng Li; Xing Zhang; Chun-Xiao Chen (Gastroenterology Research and Practice)
Background. The diagnosis of isolated small bowel Crohn’s disease (ISBCD) has always been challenging. Aims. This study is aimed at comparing the clinical features and double-balloon enteroscopy (DBE) characteristics of ISBCD with those of other small bowel ulcerative diseases (OSBUD). Methods. Patients with coexisting colonic and/or ileal valve lesions (n=45) or whose final diagnosis was not determined (n=29) were excluded. One hundred thirty-nine patients with ISBCD and 62 patients with OSBUD found by DBE were retrospectively analyzed. Results. The age of ISBCD onset was lower than that of OSBUD (OR 0.957, 95% CI 0.938-0.977, p<0.001). Abdominal pain was more common in ISBCD (OR 4.986, 95% CI 2.539-9.792, p<0.001). Elevated fibrinogen levels (OR 1.431, 95% CI 1.022-2.003, p=0.037) and lower levels of D-dimer (OR 0.999, 95% CI 0.999-1.000, p=0.017) were also more supportive of the diagnosis of ISBCD. Nonsteroidal anti-inflammatory drugs (NSAIDs) used for more than two weeks decreased the probability of a diagnosis of ISBCD (OR 0.173, 95% CI 0.043-0.695, p=0.013). Abdominal computed tomography revealed a higher proportion of skip lesions in ISBCD than in OSBUD (OR 9.728, 95% CI 3.676-25.742, p<0.001). The ulcers of ISBCD were more distributed in the ileum (111 (79.9%) vs. 29 (46.8%), p<0.001), and their main morphology differed in different intestinal segments. Longitudinal ulcers (OR 14.293, 95% CI 4.920-41.518, p<0.001) and large ulcer (OR 0.128, 95% CI 0.044-0.374, p<0.001) contributed to the differentiation of ISBCD from OSBUD. We constructed a diagnostic model, ISBCD index (AUROC=0.877, 95% CI: 0.830-0.925), using multifactorial binary logistic regression to help distinguish between these two groups of diseases. Conclusion. Clinical features, laboratory tests, abdominal computed tomography, DBE characteristics, and pathology help to distinguish ISBCD from OSBUD.